Retirement and work from the perspective of psychology in the Latin America: a scope review - da Silva Silveira, Gabriel; Barros, Leonardo de Oliveira (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
Recent changes in the Brazilian Constitution have affected the world of work, so that authors in the field of Psychology have been trying to understand important career phenomena, including retirement. The aim of this investigation was to carry out a scope review of Latin American literature on retirement and work from the perspective of Psychology. Empirical articles extracted from the following databases were analyzed: SciELO, Google Scholar, Portal de Periódicos CAPES, LILACS and Redalyc. The descriptors “aposentadoria e trabalho”, “retirement and work” and “jubilación y trabajo” were used. The results indicated a greater predominance of studies by Brazilian authors, more qualitative investigations and more studies in the field of Clinical/Vocational Psychology. There was also a growing amount of research that sought to understand the influences of social and family relationships on the decision and implications of retirement. It is concluded that it is necessary to carry out research associating retirement with important career variables.